Legal Implications of the Territorial Principle on Cross-Border Insolvency in Indonesian Bankruptcy Law - Hikmah, Nurul (Justice Voice, 2024)
Economic development across countries plays a crucial role in shaping an economic system that adapts to changing times. However, economic activities are inherently linked to various transactions, which may result in companies facing challenges, losses, or even bankruptcy. In Indonesia, bankruptcy regulations are governed by Law No. 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations. Indonesia adheres to a territorial principle in handling cross-border insolvency cases, which affects the authority of the trustee and the rights of creditors. This study aims to analyze the legal framework and implications of applying the territorial principle in cross-border insolvency. The findings suggest that the application of the territorial principle exacerbates difficulties and complexities for the trustee in managing the debtor’s bankrupt assets. Furthermore, creditors experience more significant losses. Thus, the territorial principle in cross-border insolvency tends to complicate the trustee’s responsibilities and place creditors at a disadvantage.